2012
DOI: 10.1089/end.2012.0308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic Experience on the Proficiency Gain of Urologic Surgeons in Robot-Assisted Surgery

Abstract: Our data indicate that familiarity with laparoscopic surgery is not associated with any advantage in learning the most fundamental techniques of robot-assisted surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This score comparison showed that robot-assisted surgical skills were retained regardless of experience or certification (Table 3, Table 4). Combined with the results of our previous report, 5 our current findings suggest that robot-assisted surgery might be suitable for urologists without training or experience with laparoscopic surgery.…”
Section: Figsupporting
confidence: 84%
See 3 more Smart Citations
“…This score comparison showed that robot-assisted surgical skills were retained regardless of experience or certification (Table 3, Table 4). Combined with the results of our previous report, 5 our current findings suggest that robot-assisted surgery might be suitable for urologists without training or experience with laparoscopic surgery.…”
Section: Figsupporting
confidence: 84%
“…5 Participants were given 2 to 3 minutes to develop familiarity with the platform and the task prior to starting the first trial. All participants completed the program 4 consecutive times, with intervals for several minutes and then a fifth trial was completed 1 year later ( Fig.…”
Section: Simulator and Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, when Teishima and colleagues compared certified expert laparoscopic urologists with novice laparoscopic urologists, significant differences in their performance on the suture sponge task of the dV-Trainer were only seen at the second and third trials, while there were no significant differences between the two groups at the first and fourth attempts. 17 This has several implications. First, even expert laparoscopic surgeons may need to become familiar with the robotic platform by performing a specific task.…”
Section: Discussionmentioning
confidence: 99%